2009
DOI: 10.1016/j.ijimpeng.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Low velocity impact on CFRP plates with compressive preload: Test and modelling

Abstract: When laminated composite materials in modern aircraft structures are subject to impact loads, they are typically not unloaded but under a certain state of prestress. Therefore, in this study the effect of a compressive preload on the low velocity impact behaviour of three different carbon fibre-reinforced plastic (CFRP) materials is investigated. An experimental test programme is documented first, including the design of a preload test device, the specimen manufacture and the results description. An increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
111
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 27 publications
7
111
0
Order By: Relevance
“…A relatively small number of studies have analysed the behaviour of preloaded structures subjected to low-velocity impacts (Nettles et al, 1995;Whittingham et al, 2004;Herszberg and Weller, 2006;Heimbs et al, 2009;Minak et al, 2010). Some of these focus on plates undergoing a uniaxially in-plane load, tensile (Nettles et al, 1995) or compressive (Whittingham et al, 2004), subjected to a transversal impacts.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively small number of studies have analysed the behaviour of preloaded structures subjected to low-velocity impacts (Nettles et al, 1995;Whittingham et al, 2004;Herszberg and Weller, 2006;Heimbs et al, 2009;Minak et al, 2010). Some of these focus on plates undergoing a uniaxially in-plane load, tensile (Nettles et al, 1995) or compressive (Whittingham et al, 2004), subjected to a transversal impacts.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that two different tensile damage modes are produced after different impact energies. Heimbs et al (2009) studied impact load coupled with a prestress condition and found that delamination is a major energy absorption mechanism.…”
mentioning
confidence: 99%
“…The main advantage of this modeling technique is the revocation of aspect ratio restrictions concerning the in-plane and through thickness element dimensions, presenting obvious advantages in regard to simulation accuracy and computational efficiency, compared to traditional modeling techniques. In the studies [8][9][10][11][12][13][14] of the literature the use of the stacked shell method has been reported for the simulation of composite laminates.…”
Section: Introductionmentioning
confidence: 99%